The multiplatform news gap: audience consumption and gratifications on websites, net-works and apps. Case study of elDiario.es - Castro-Pérez, Iago; Diez-Gracia, Alba; Sánchez-García, Pilar (Estudios sobre el Mensaje Periodístico, 2022)
The evolution of smartphones drives the consumption of information on digital platforms, where social networks and apps take relevance as communicative channels. This justifies the need to permanently investigate the variation of the uses and gratifications in the digital audience. This study delves into the information gap generated by analysing the audience's selection, preference and interest in the content offered on multiplatform -web, social networks and apps- to determine whether or not they follow the agenda set by the media. Thus, it proposes a case study with a double methodology of content analysis (N=210) applied to elDiario.es; and a survey (N=245) on the audience's consumption of networks and apps. The results confirm this gap and the divergence in uses and gratifications together with a media strategy that is not very specialised in mobile and networks, while the audience highlights them as relevant for their information consumption
Keywords: uses and gratifications; elDiario.es; Information gap; Mobile journalism; Multiplatform; Gender; mass media; agenda setting; framing; social networks.